If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(k + -2) + -3(k + -6) = 0 Reorder the terms: 5(-2 + k) + -3(k + -6) = 0 (-2 * 5 + k * 5) + -3(k + -6) = 0 (-10 + 5k) + -3(k + -6) = 0 Reorder the terms: -10 + 5k + -3(-6 + k) = 0 -10 + 5k + (-6 * -3 + k * -3) = 0 -10 + 5k + (18 + -3k) = 0 Reorder the terms: -10 + 18 + 5k + -3k = 0 Combine like terms: -10 + 18 = 8 8 + 5k + -3k = 0 Combine like terms: 5k + -3k = 2k 8 + 2k = 0 Solving 8 + 2k = 0 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + 2k = 0 + -8 Combine like terms: 8 + -8 = 0 0 + 2k = 0 + -8 2k = 0 + -8 Combine like terms: 0 + -8 = -8 2k = -8 Divide each side by '2'. k = -4 Simplifying k = -4
| .4/m=2/4.5 | | 7x+49=175 | | -6(1+11b)=-138 | | -8.5n+4.7=328.55 | | 5(k-2)-4(m+3)=0 | | 2(2x+.33)=.5(x+5.33) | | -8.5+4.7=328.55 | | 9/15=3x/10 | | 16x^2-121x+576=0 | | 9x-15y=8 | | y=15-.025x | | 7/10=×/50 | | 5x=4(10x) | | 2x+6=-5x+3 | | 4x+40=-20 | | x-2(x+3y)-(2x+3y)-4(x+y)= | | 5x+8=14-3x | | 10x-15=5(2+3x) | | -12=5b/8 | | 4(8n+2)=40 | | -0.9y+8.5=43.6 | | 9x+-2=43 | | 16x^4+8x^3=0 | | 10/2.4=p/2.64 | | -6n+10=46 | | 3(4+3r)=18 | | -2x(x-3)+4x=-(-x+1) | | (-8a)(-3/4) | | R/10=21/7 | | -48=7(7a+7)+3(8a-8) | | 1/9x-15=5 | | -6.9b+7.2=335.64 |